MADRASAH PRINCIPAL’S MANGERIAL COMPETENCE IN ENHANCING STUDENT INTEGRITY DURING THE IMPLEMENTATION OF COMPUTER-BASED TESTS (CBT) - Syeh Nuruddin Daulah; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study examines the contribution of Madrasah Principal’s mangerial Competence to strengthening students' academic integrity during Computer-Based Testing (CBT). Although CBT offers efficiency and accuracy in assessment systems, digitalization introduces new challenges in the form of technology-based cheating, such as the unauthorized use of dual devices. Utilizing a qualitative approach through library research, data were gathered from various scholarly journals and reference books, and subsequently evaluated using content analysis. The findings indicate that digital security systems require comprehensive managerial intervention from institutional leaders to function optimally; thus, this study formulates three primary managerial pillars to maintain student honesty within the CBT ecosystem. These three pillars encompass integrated planning and organizing that balances digital infrastructure readiness with the embedding of Islamic educational values as a moral foundation; the expansion of academic supervision into proactive hybrid monitoring to close loopholes for manipulation in digital exams; and a synergy between technological protection and religiosity that pairs security software, such as Safe Exam Browser, with the internalizations of religious values to foster students' internal moral control (Moral Action). Overall, this study underscores the crucial role of the madrasah principal as a moral architect capable of blending sophisticated technological innovation with religious values to create an honest, credible, and accountable digital evaluation ecosystem